Breath biomarkers of inflammation, infection and metabolic derangement in the intensive care unit - Sturney, Sharon C. (2015)
The analysis of volatile organic compounds (VOCs) in breath may be a useful non-invasive tool in the Intensive Care Unit (ICU) to monitor metabolic and oxidative stress or diagnose pulmonary infection. Acetone is produced during starvation and metabolic stress, hydrogen sulphide (H2S) may be a marker of inflammation and infection and hydrogen cyanide (HCN) may also act as a marker of infection, particularly caused by Pseudomonas aeruginosa.